PENERAPAN METODE CERAMAH BERVARIASI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA DI KELAS IV SDN 43 AMPENANTAHUN AJARAN 2016/2017 - Reza Pahlevi; Ratnadi Ratnadi; Muhammad Makki; Safruddin Safruddin (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2020)
The purpose of this study is to apply various lecture methods to improve student achievement in class IV in the Science Subjects of SDN 43 Ampenan for the 2016/2017 academic year. This type of research is Classroom Action Research (CAR). In this classroom action research, improvements are made gradually and continuously during the research activities. This research was carried out at SDN 43 Ampenan which is located in Sekarbela District, Mataram City, West Nusa Tenggara Province. This research was conducted in the odd semester of the 2016/2017 Academic Year. On September 7-17, 2016. The subjects of this class action research were fourth grade students at SDN 43 Ampenan, totaling 38 students consisting of 19 male students and 19 female students. The observer in this study was the homeroom teacher of class IV. Classroom Action Research. Therefore, the procedure of this research is planning, implementation, observation and reflection. The instruments used in this research are as follows: (1) Test; and (2) observation sheet. Data collection techniques in this study are: (1) test; (2) observation; and (3) documentation. Data were analyzed through various methods to see student learning outcomes before and after treatment, student activity data, and teacher activities. the application of the Varied Lecture Method can improve the science learning outcomes of fourth grade students at SDN 43 Ampenan for the 2016/2017 academic year, as seen by the increase in the class average for the first cycle, which is 69.21 with classical completeness of 78.94%. It increased in the second cycle, the class average was 74.21, an increase of 5 points from the first cycle and the increase in classical completeness was 86.84%, an increase of 7.9 points from the first cycle. For other researchers who want to research by applying the Varied Lecture Method, it is hoped that they can apply it in different classes and in different subjects.